107k views
0 votes
Haeeelllppp 9b-14b+5

User Kauppfbi
by
5.5k points

1 Answer

6 votes

Answer:

Explanation:

Simplifying

5 + 14b = 9b + -5

Reorder the terms:

5 + 14b = -5 + 9b

Solving

5 + 14b = -5 + 9b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-9b' to each side of the equation.

5 + 14b + -9b = -5 + 9b + -9b

Combine like terms: 14b + -9b = 5b

5 + 5b = -5 + 9b + -9b

Combine like terms: 9b + -9b = 0

5 + 5b = -5 + 0

5 + 5b = -5

Add '-5' to each side of the equation.

5 + -5 + 5b = -5 + -5

Combine like terms: 5 + -5 = 0

0 + 5b = -5 + -5

5b = -5 + -5

Combine like terms: -5 + -5 = -10

5b = -10

Divide each side by '5'.

b = -2

Simplifying

b = -2

User Paul Mikesell
by
4.6k points